Inhibition of Streptococcus pyogenes growth by native Australian plants: New approaches towards the management of impetigo, pharyngitis and rheumatic heart disease - Lee, Cameron Jay; Wright, Mitchell Henry; Arnold, Megan Sarah Jean; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Streptococcus pyogenes can cause a variety of diseases including streptococcal pharyngitis, impetigo and rheumatic heart dis- ease, dependant on which tissue it infects. Many Australian plants have documented therapeutic properties as general antiseptics, but are yet to be tested for the ability to inhibit S. pyogenes growth. Methods: Solvent extracts were prepared using Australian plants with documented ethnobo- tanical usage to treat bacterial infections, or published antibacterial activ- ity. The extracts were investigated by disc diffusion assay for the ability to inhibit the growth of a clinical strain of S. pyogenes. Their MIC values were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: S. pyogenes growth was inhibited by 24 of the 34 extracts tested. The Euca- lyptus spp. extracts were particularly potent. MIC values of 341 and 88 µg/ mL were determined for the aqueous and methanolic E. baileyana extracts respectively. Similarly, MIC values of 134 and 53 µg/mL were determined for the aqueous and methanolic E. major extracts respectively. The metha- nolic wattle seed extract, aqueous and methanolic lemon aspen extracts, aqueous native thyme extract, methanolic river mint extract and the metha- nolic native basil extract were similarly potent growth inhibitors, with MIC values ≤1000 µg/mL. Several other extracts (methanolic native tamarind, bush tomato, desert lime, native thyme, native sage and the T. stipitata leaf extracts, as well as the aqueous river mint, native basil, T. stipitata leaf extracts) displayed moderate growth inhibitory activity (MIC=1000-5000 µg/mL). All other extracts were either low potency S. pyogenes growth inhibitors or were devoid of inhibitory activity. The E. baileyana and E. major methanolic extracts, as well as the E. baileyana aqueous extract induced significant mortality in the Artemia fransiscana bioassay, with LC50 values substantially <1000 µg/mL. All other extracts were nontoxic, with LC50 val- ues >1000 µg/mL. Conclusion: The potent growth inhibitory bioactivity of the Eucalyptus spp., lemon aspen, wattle seed, native basil and river mint extracts against S. pyogenes demonstrates their potential for the treat- ment and prevention of S. pyogenes induced disease. However, the toxic- ity of the Eucalyptus spp. extracts may limit their use to topical treatments for pharyngitis and impetigo. As the lemon aspen, wattle seed, native basil and river mint extracts were nontoxic, they may also have wider uses in treating systemic illnesses such as rheumatic fever, rheumatic heart dis- ease and cellulitis.
Keywords: Eucalyptus; Antioxidant; Lemon aspen; Pharyngitis; Impetigo; Rheumatic heart disease; Antibacterial activity